2005
DOI: 10.3989/scimar.2005.69n2215
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium, rubidium and potassium in <i>Octopus vulgaris</i> (Mollusca: Cephalopoda)

Abstract: SUMMARY: The levels of vanadium, rubidium and potassium were determined in Octopus vulgaris caught during commercial fishing activities at three locations (Cascais, Santa Luzia and Viana do Castelo) in Portugal in autumn and spring. We determined the concentration of these elements in digestive gland, branchial heart, gills, mantle and arms in males and females. At least five males and five females were assessed for each season/location combination. Elemental concentrations were determined by Particle Induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Agusa et al ,49 on the other hand, reported higher Rb than Sr levels in some fish species from several locations in Cambodia, Indonesia and Thailand. In a study by Seixas and Pierce,50 Octopus vulgaris showed Rb levels between 3 and 5 mg kg −1 dry weight, somewhat higher than those found in N. norvegicus . Species of Lamellibranchiata and Gastropoda showed similar levels of Sr to those observed in N. norvegicus in the present study 37.…”
Section: Resultsmentioning
confidence: 76%
“…Agusa et al ,49 on the other hand, reported higher Rb than Sr levels in some fish species from several locations in Cambodia, Indonesia and Thailand. In a study by Seixas and Pierce,50 Octopus vulgaris showed Rb levels between 3 and 5 mg kg −1 dry weight, somewhat higher than those found in N. norvegicus . Species of Lamellibranchiata and Gastropoda showed similar levels of Sr to those observed in N. norvegicus in the present study 37.…”
Section: Resultsmentioning
confidence: 76%
“…The study of Otachi et al (2014) reports 18.2 mg/kg Rb in muscle from O. leucostictus from Lake Naivasha. Although there is no agreement on the importance of Rb as an ultra-trace essential element to humans and other biota, some studies have shown that even low concentrations in combination with other metals such as Pb and Mo, can be toxic to fish and other organisms (Seixas and Pierce 2005;Yamaguchi et al 2007). Safe concentrations are not known and the RfDo is not given, therefore THQ was not determined for Rb.…”
Section: Elementmentioning
confidence: 99%
“…accumulation in cephalopods is far from being consensual (e.g. Barghigiani et al, 2000;Bustamante et al, 1998;Seixas and Pierce, 2005;Bustamante et al, 2006;Raimundo et al, 2010a). Presumably, other biologic or environmental factors mitigate the effect of gender on trace element accumulation.…”
Section: Discussionmentioning
confidence: 95%